Komitmen Spiritual dan Komitmen Organisasi dalam Meningkatkan Kinerja Koperasi - Indira Basalamah; Muhammad Carda P; Andi Haerani (Movere Journal, 2026)
This study aims to analyze the role of spiritual leadership and organizational commitment in improving the performance of cooperatives in Makassar City. A descriptive qualitative approach was employed, using in-depth interviews, observation, and documentation from several active cooperatives in the region. The results indicate that spiritual leadership emphasizing honesty, integrity, empathy, and responsibility positively influences the development of organizational commitment. Leaders with spiritual orientation are able to instill a sense of meaning, loyalty, and active participation among members, thereby enhancing cooperative performance in both financial and social aspects. Organizational commitment, particularly affective and normative commitment, was found to strengthen members’ sense of belonging and engagement within the cooperative. Furthermore, local cultural values such as siri’ na pacce (self-respect and compassion) reinforce the implementation of spiritual leadership in the Makassar context. Therefore, integrating spiritual leadership with organizational commitment can serve as an effective strategy to achieve sustainable cooperative performance.